THE ROLE OF ENGLISH TERMINOLOGY IN GLOBAL COMMUNICATION, AND THE ESTABLISHMENT OF ENGLISH AS THE LANGUAGE OF INTERNATIONAL SCIENCE AND COMMERCE - Makhmudova Maftuna Zafar kizi (Bright Mind Publishing, 2025)
This article explores the growing importance of English terminology in international communication and examines how English has become the dominant language in global scientific and commercial spheres. It analyzes the benefits of a shared linguistic framework for knowledge exchange and business operations while addressing the challenges related to linguistic equity, cultural diversity, and epistemological inclusion. Drawing on the latest academic research and global trends, the article advocates for a balanced, multilingual future that leverages the strengths of English while preserving linguistic plurality.
Keywords: English terminology, global communication, science, commerce, linguistic dominance, multilingualism, knowledge economy